Training for sprinting speed and acceleration (Peak Performance, 2007)
There is something incredibly pure about speed. In athletics or track and field, the 100m, 200m and 400m events produce exhilaration that the other events rarely match. Audiences worldwide appreciate speed, and the anticipation to see who is the fastest, who can break records, who can win race after race is exhilarating. One of favourite armchair sporting moments was watching Michael Johnson smash the 200m record in the 1996 Olympic final. Just watching that speed took my breath away more than running any 200m sprint ever did! It is not just in athletics where sprinting and acceleration are vital. Just think of the advantages certain athletes have in their sports because of their extra pace: Thierry Henry in football, Bryan Habana in rugby, Allen Iverson in basketball, LaDainian Tomlinson in American football. A leading factor to explain why the game looks so easy for these players is because of their electrifying speed and acceleration. There truly is no substitute for pace! This special report aims to help both track sprinters and team athletes improve their speed training. The opening chapters explain how to build a foundation for increasing your speed. The next couple of chapters take a look at specific training methods to increase acceleration and top speed, once that foundation is solid. There is an article on 'the 40', a very popular test in America judging relevant speed. The final two chapters explain how you can strengthen those legs to avoid injuries and gain even more power out of the blocks.